2020
DOI: 10.1002/bjs.11530
|View full text |Cite
|
Sign up to set email alerts
|

Delphi prioritization and development of global surgery guidelines for the prevention of surgical-site infection

Abstract: Background Most clinical guidelines are developed by high‐income country institutions with little consideration given to either the evidence base for interventions in low‐ and middle‐income countries (LMICs), or the specific challenges LMIC health systems may face in implementing recommendations. The aim of this study was to prioritize topics for future global surgery guidelines and then to develop a guideline for the top ranked topic. Methods A Delphi exercise identified and prioritized topics for guideline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…In one study, a positive correlation was found between microbial air contamination and the number of people in the operating room and number of door openings [120]. Global surgery guidelines for the prevention of SSI have been suggested [121], leading to an expectation among surgeons of 100% adherence to pre-established protocols (standards) throughout a surgery, although this bar is a difficult one for all personnel to meet [122][123][124].…”
Section: Team Personnelmentioning
confidence: 99%
“…In one study, a positive correlation was found between microbial air contamination and the number of people in the operating room and number of door openings [120]. Global surgery guidelines for the prevention of SSI have been suggested [121], leading to an expectation among surgeons of 100% adherence to pre-established protocols (standards) throughout a surgery, although this bar is a difficult one for all personnel to meet [122][123][124].…”
Section: Team Personnelmentioning
confidence: 99%
“…The global burden of morbidity as a result of surgical infection has dramatic and wide-reaching effects on patients, providers, and health systems in LMICs [14,61,62]. SSI has therefore been recognised as the highest global priority in surgical research and is therefore a natural target for the TALON study [7,63]. Future work will be required to standard processes for outcome assessment across other common and severe postoperative complications [64].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of findings into 'Essential Global Surgical Guidelines' will help clinicians to influence care providers and hospital managers and deliver impactful SSI prevention measures across borders. 20 This will be the key step in reducing the volume of antimicrobial agents used in the perioperative setting, and mitigating against the rise of multi-drug resistance in years to come.…”
Section: Editorialmentioning
confidence: 99%